The impact of climate change on hydrological predictions, with specific reference to 24-hour rainfall intensities in the Western Cape - Van Wageningen, Andries (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2006.